Voxelization and one-dimensional lattice structures for industrial components using function representation - Antonio Bacciaglia; Alfredo Liverani; Alessandro Ceruti (Virtual and Physical Prototyping)
This paper presents a scalable, open-source method for designing strut-and-node lattice structures for industrial applications, including uniform and graded lattices. Traditional computer-aided design tools struggle with lattice structures with high complexity, prompting the need for alternative approaches. While function representation techniques are commonly applied to triply periodic minimal surface lattices, their use for strut-and-node lattices has been limited. The proposed method defines the unit cell geometry using function representation primitives to model cylindrical struts and spheres, followed by isosurface triangulation and spatial replication within a voxelized design space. To showcase its practical application, two case studies are presented in which industrial components are filled with uniform and graded lattice structures using the newly developed model. The paper includes a comprehensive analysis of the computational cost of the approach. Furthermore, the study evaluates the geometric accuracy and quality of the generated lattice, highlighting their suitability for lightweight design in additive manufacturing. This method eliminates the need for boundary representations of lattice structure models, leading to more efficient data handling. The results of this research have broad implications for developing 3D components optimised for additive manufacturing. The approach targets industrial use, enabling fast, efficient design of complex, lightweight geometries.